Healthcare professionals' experiences and perceptions regarding health care of indigenous pregnant women in Ecuador - Tannia Valeria Carpio-Arias; Nervo Verdezoto; Marta Guijarro-Garvi; Victoria Abril-Ulloa; Nicola Mackintosh; Parisa Eslambolchilar; María Teresa Ruíz-Cantero (BMC, 2022)
Abstract Background Pregnancy is an important life experience that requires uniquely tailored approach to health care. The socio-cultural care practices of indigenous pregnant women (IPW) are passed along the maternal line with respect to identity, worldview and nature. The cultural differences between non-indigenous healthcare professionals (HPs) and IPW could present a great challenge in women's health care. This article presents an analysis from a human rights and gender perspective of this potential cultural divide that could affect the health of the IPW in an Andean region of Ecuador with the objective of describing the health challenges of IPWs as rights holders through the experiences and perceptions of HP as guarantors of rights. Methods We conducted 15 in-depth interviews with HPs who care for IPW in Chimborazo, Pichincha provinces of Ecuador. We utilized a semi-structured interview guide including questions about the experiences and perceptions of HPs in delivering health care to IPW. The interviews were recorded, transcribed and subjected to thematic analysis in Spanish and translated for reporting. Results We found disagreements and discrepancies in the Ecuadorian health service that led to the ignorance of indigenous cultural values. Common characteristics among the indigenous population such as illiteracy, low income and the age of pregnancy are important challenges for the health system. The gender approach highlights the enormous challenges: machismo, gender stereotypes and communication problems that IPWs face in accessing quality healthcare. Conclusions Understanding the diverse perspectives of IPW, acknowledging their human rights particularly those related to gender, has the potential to lead to more comprehensive and respectful health care delivery in Ecuador. Further, recognizing there is a gender and power differential between the provider and the IPW can lead to improvements in the quality of health care delivery and reproductive, maternal and child health outcomes.